Lessons From COVID-19 Responses in East Asia: Institutional Infrastructure and Enduring Policy Instruments. Issue 6 (August 2020) - An, Brian Y.; Tang, Shui-Yan
Existing commentaries on government responses to COVID-19 have focused on such factors as competent leadership, policy instruments, or cultural dispositions. Yet, few have provided a synthesis that examines how these factors relate to each other. This article fills this gap in the debate by comparing COVID-19 responses among five advanced economies in East Asia: Taiwan, Hong Kong, South Korea, Singapore, and Japan. Although agile actions and competence of top leadership are necessary to confront an unprecedented crisis, they are by themselves insufficient. Equally critical is whether a society has the necessary institutional infrastructure in place when a crisis strikes. Policy instruments are more likely to succeed when existing institutional infrastructure supports their administration and implementation. For an instrument to generate enduring impact, it must be compatible with a polity's underlying culture; instruments that accommodate the underlying cultural orientations are more likely to elicit public cooperation and voluntary compliance over time. Policy instruments must also address equity issues by reaching marginalized groups across all layers of the population. Progress in emergency management may be visible in mainstream society but masking brewing problems among marginalized groups. A comparison across the five advanced economies in East Asia yields several implications for comparative research and policy.